ANALISIS EFISIENSI DAN EFEKTIVITAS PENGELOLAAN PERSEDIAAN PADA APOTEK GRATIA LAMPUNG TENGAH - Yohannes Suharsana; Ignasia Natalelawati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
The purpose of this research is to control inventory by using two method of measurement that isinventory turnover and number of day's sales in inventory with data collecting method in this research isby interview, documentation and doing library research.Data used in this research is primary data that is data obtained directly from first source orplace of research object that is from Apotek Gratia. And with the type of research that uses is a methodof quantitative analysis and qualitative analysis methods. Data analysis technique used in this researchis quantitative analysis with calculation Ratio of Inventory Turnover. After that based on the results ofthe calculation of 20 products sampled described by the difference of average age of inventory less thanor equal to than 22 days declared effective and efficient whereas if the average age of inventory morethan 22 days declared ineffective and efficient.The product used as a sample of 20 products from 4 groups in 2015 - 2016 has been largelydeclared effective and efficient in inventory management. Based on the calculation of InventoryTurnover Ratio 20 of the sampled products show the difference in average days of inventory less thanor equal to 22 days.Looking at the results by calculating Inventory Turnover and the statement that Gratia Drugtrokeis effective and efficient in inventory management although it has not used this method in determiningthe amount of inventory but it is still advisable to use this method in inventory control for non-sampelproduct inventory.